2019
DOI: 10.3390/jcm8101619
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Nocturnal Cardiovascular Variability and Heart Rate Arousal Response in Restless Legs Syndrome (RLS)/Periodic Limb Movements (PLMS)

Abstract: Recent studies have suggested that restless legs syndrome is associated with an increased prevalence of cardiovascular diseases mediated by sympathetic activation occurring during periodic limb movements. The aim of this study was to establish which factors affect the degree of sympathetic activation during the basal condition and during periodic limb movements that may contribute to increased vascular risk. Fifty untreated restless legs syndrome patients aged 62.6 ± 11.1 y, free of cardiovascular diseases, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…There are increasing evidence that vitamin D can regulate the circadian rhythm of sleep ( 41 , 42 ). Several magnetic resonance imaging (MRI) studies had revealed an increased glutamic acid in the thalamus of RLS patients, which also was associated with sleep quality ( 43 45 ), providing insight into the role of glutamate and dopamine in regulating sleep–wake disorder ( 46 ). The pathogenesis of the regulatory role of vitamin D in sleep disorder with RLS patients is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…There are increasing evidence that vitamin D can regulate the circadian rhythm of sleep ( 41 , 42 ). Several magnetic resonance imaging (MRI) studies had revealed an increased glutamic acid in the thalamus of RLS patients, which also was associated with sleep quality ( 43 45 ), providing insight into the role of glutamate and dopamine in regulating sleep–wake disorder ( 46 ). The pathogenesis of the regulatory role of vitamin D in sleep disorder with RLS patients is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The repeated increase in nocturnal heart rate and blood pressure are considered to be the reason for the negative influence of PLMS on the cardiovascular system. Nevertheless, some researchers deny the existence of persistent sympathetic hyperactivity in the absence of movement (in other words, sympathetic hyperactivity exists only when PLMS occurs) ( 37 , 38 ). On the other hand, other authors highlighted the primary role of the sympathetic nervous system in the generation of PLMS ( 39 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, three papers explored the role of ANS in acute and chronic neurological disorders, such as Restless Legs Syndrome/Periodic Limb Movements, stroke, and multiple sclerosis. The study by Sforza and colleagues showed that a significant increase in sympathetic activity occurred in periods with periodic limb movements and electromyogram power is the factor that affects sympathetic control [ 5 ]. Lin et al observed that baroreflex sensitivity can predict functional outcomes and complications after acute ischemic stroke [ 6 ].…”
mentioning
confidence: 99%